DESIGN OF WIND POWER PLANTS USING SAVONIUS-DARRIEUS TURBINES WITH MAGNETIC POLE GENERATORS - Okvani, Ahmad; Firman Yasa Utama (Indonesian Journal of Engineering and Technology (INAJET), 2025)
The utilization of wind energy as a renewable energy source presents a strategic solution to address the limitations of fossil fuel resources and the growing demand for energy. This study aims to design and test a hybrid Savonius-Darrieus Wind Power Plant (WPP) prototype equipped with a variable magnetic pole generator to optimize the conversion of fluctuating wind energy into electrical energy. The research method employed is Research and Development (R&D), comprising stages of literature review, 2D and 3D design, prototype assembly, and functional testing conducted in the coastal area of Kenjeran Beach, Surabaya. The testing involved variations in the number of magnetic poles (2 and 4) and pulley ratios (2:1 and 3:1), using an anemometer and multimeter for measurement. The results of the study produced a complete design of the Savonius-Darrieus WPP prototype with a length of 100 cm, a width of 100 cm, and a height of 80 cm. The generator used is a permanent magnet generator based on an AC fan motor dynamo type YYW25-6-17004L, utilizing coin-type neodymium magnets with a diameter of 1 cm and a thickness of 0.6 cm.